Investigating Non-sterilizing Cure in TB Patients at the End of Successful Anti-TB Therapy - Beltran, Caroline G. G.; Heunis, Tiaan; Gallant, James; Venter, Rouxjeane; du Plessis, Nelita; Loxton, Andre G.; Trost, Matthias; Winter, Jill; Malherbe, Stephanus T.; Kana, Bavesh D.; Walzl, Gerhard (Frontiers in Cellular and Infection Microbiology, 2020)
Mycobacterium tuberculosis (Mtb) is extremely recalcitrant to antimicrobial chemotherapy requiring 6-months to treat drug-sensitive tuberculosis (TB). Despite this, 4-10% of cured patients will develop recurrent disease within 12 months after completing therapy. Reasons for relapse in cured TB patients remains speculative, attributed to both pathogen and host factors. Populations of dormant bacilli are hypothesized to cause relapse in initially cured TB patients however, development of tests to convincingly demonstrate their presence at the end of anti-TB treatment has been challenging. Previous studies have indicated the utility of culture filtrate supplemented media (CFSM) to detect differentially culturable tubercle bacilli (DCTB). Here, we show that 3/22 of clinically cured patients retained DCTB in induced sputum and bronchoalveolar lavage fluid (BALF), with one DCTB positive patient relapsing within the first year of completing therapy. We also show a correlation of DCTB status with ‘unresolved’ end of treatment FDG PET-CT imaging. Additionally, 19 end of treatment induced sputum samples from patients not undergoing bronchoscopy were assessed for DCTB, identifying a further relapse case with DCTB. We further show that induced sputum is a less reliable source for the DCTB assay at the end of treatment, limiting the utility of this assay in a clinical setting. We next investigated the host proteome at the site of disease (BALF) using multiplexed proteomic analysis and compared these to active TB cases to identify host-specific factors indicative of cure. Distinct signatures stratified active from cured TB patients into distinct groups, with a DCTB positive, subsequently relapsing, end of treatment patient showing a proteomic signature closer to active TB disease than cure. This exploratory study offers evidence of live Mtb, undetectable with conventional culture methods, at the end of clinically successful treatment and putative host protein biomarkers of active disease and cure. These findings have implications for the assessment of true sterilizing cure in TB patients and opens new avenues for targeted approaches to monitor treatment response.